Pregnancy onset congenital thrombotic thrombocytopenic purpura (Upshaw-Schulman syndrome) mimicking HELLP syndrome: a case report - Başak Ergin; Berna Buse Kobal; Zeynep Yazıcı; Ali Hakan Kaya; Sezin Canbek; Murat Muhcu; Ayşegül Özel (Perinatal Medicine Foundation, 2021)
Objective Thrombotic thrombocytopenic purpura is a thrombotic microangiopathic condition characterized by hemolytic anemia, thrombocytopenia, neurologic abnormalities, fever and renal dysfunction. Thrombotic microangiopathies such as preeclampsia and HELLP syndrome are pregnancy-specific, whereas others such as thrombotic thrombocytopenic purpura (TTP) and hemolytic uremic syndrome are not. In this report, we present a case at which we identified a novel mutation which led to a significant reduction of ADAMTS13 activity. Case(s) A nulliparous pregnant woman of 32-year-old presenting with epigastric pain, hypertension and low platelet count was first suspected of HELLP syndrome, but was diagnosed with congenital TTP after delivery. Conclusion HELLP syndrome co-existed with undiagnosed TTP in this case. We strive to have sufficient awareness in order to distinguish these two pathologies from each other on an antenatal basis, because the causes of the managements are entirely different.